Soil Aggregate Dynamics Influenced by Biochar Addition using the 13C Natural Abundance Method. Issue 3 (30th June 2017) - Yoo, Gayoung; Kim, Hyunjin; Choi, Jong Yun
Abstract : Understanding the mechanisms of biochar C sequestration within soil aggregates requires us to investigate the role of biochar in the soil aggregation process. We aimed to compare aggregate dynamics in soils amended with organic matter or with biochar and to quantify the amount of biochar and organic matter included in different sizes of aggregate. In free‐draining incubation jars, soils collected from grassland and rice ( Oryza sativa L.) paddy were amended with fresh corn stalks ( Zea mays L) and leaves (CORN_RAW) and with biochar made from corn stalks and leaves (CORN_CHAR). Temporal change in the aggregates were investigated. Soils were fractionated into macroaggregates (250–1000 μm), microaggregates (53–250 μm), and organo‐mineral complexes (<53 μm). The added materials were measured using the difference in the relative depletion of 13 C (δ 13 C) values between the soil and the amendments. Although the macroaggregates in the CORN_RAW treatment increased throughout the incubation period, those in the CORN_CHAR treatment only increased during the initial 60 d. This indicates that macroaggregates in biochar‐amended soil might not be stable enough. However, microaggregates in the CORN_CHAR treatment showed an increase of >200% throughout the incubation period, probably as a result of the breakdown of macroaggregates and formation through chemical adsorptive interactions between biochar surface and soil particles. The proportion of biochar‐derived C within aggregates was greatly increased by 204% on average from the initial to later periods, indicating that biochar C is preferentially enriched because of its chemical recalcitrance and physical occlusion within the aggregates. The overall results imply that biochar amendment could initiate macroaggregation; however, the temporal change pattern was different. Biochar C could be both chemically and physically protected from decomposition during long‐term sequestration.